2019
DOI: 10.1186/s12884-019-2665-0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections in pregnancy in a rural population of Bangladesh: population-based prevalence, risk factors, etiology, and antibiotic resistance

Abstract: BackgroundUrinary tract infection (UTI) in pregnancy, including asymptomatic bacteriuria, is associated with maternal morbidity and adverse pregnancy outcomes, including preterm birth and low birthweight. In low-middle income countries (LMICs), the capacity for screening and treatment of UTIs is limited. The objective of this study was to describe the population-based prevalence, risk factors, etiology and antimicrobial resistance patterns of UTIs in pregnancy in Bangladesh.MethodsIn a community-based cohort i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
63
5
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(105 citation statements)
references
References 41 publications
(44 reference statements)
12
63
5
11
Order By: Relevance
“…E.coli and Pseudomonas aeruginosa were 100% resistant to both Ampicillin and Amoxicillin. This has been demonstrated in other studies in Ethiopia, Kenya, Tanzania and Uganda at Mulago National Referral Hospital though the level of resistance was much higher than reported in most of the mentioned studies (8,10,13,16,17). The high resistance could be attributed to the over-the counter availability of these drugs particularly Ampicillin and Amoxicillin.…”
Section: Discussionsupporting
confidence: 51%
“…E.coli and Pseudomonas aeruginosa were 100% resistant to both Ampicillin and Amoxicillin. This has been demonstrated in other studies in Ethiopia, Kenya, Tanzania and Uganda at Mulago National Referral Hospital though the level of resistance was much higher than reported in most of the mentioned studies (8,10,13,16,17). The high resistance could be attributed to the over-the counter availability of these drugs particularly Ampicillin and Amoxicillin.…”
Section: Discussionsupporting
confidence: 51%
“…They also reported bacteriuria due to staphylococcal (23% of isolates) and Group B streptococcus species (5.3% of isolates). 35 Similarly, Majumder et al. 44 and Haque et al.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, a study conducted in Bangladesh on UTI in pregnant women reported high-burden bacteriuria (5.7%) in both symptomatic and asymptomatic cases. 35 Similarly, Dashtizade et al. 36 also reported the prevalence of UTI in Iranian pregnant women.…”
Section: Discussionmentioning
confidence: 95%
“…Introduction / Введение Urinary tract infection (UTI) is a common clinical problem and is an infection caused by the presence and growth of microorganisms in the urinary tract. It affects all age groups but women are more susceptible than men due to their short urethra, absence of prostatic secretion, pregnancy and easy contamination of the urinary tract with faecal flora [1]. UTI is the second common infection occurring during pregnancy [2].…”
Section: акушерство гинекология и репродукцияmentioning
confidence: 99%
“…Several microorganisms have been associated with UTI although Escherichia coli is the most frequent accounting for 80 % to 90 % of UTI's in pregnancy [1,[9][10][11].…”
Section: акушерство гинекология и репродукцияmentioning
confidence: 99%